Developmental regulation of the monoamine fear circuitry - Jacobsen, Kirsten (University of Ottawa (Canada), 2008)
The central thesis of these studies was to examine the regulatory mechanisms that govern the development of neurotransmitter systems of the mammalian monoamine fear circuitry. We first examined the central orchestrator of the monoamine fear circuitry, the extended amygdala, comprised of the amygdala proper, as well as its rostral extension along the bed nucleus of the stria terminalis to the shell of the nucleus accumbens. We identified a series of GABAergic gating structures along the entire rostro-caudal axis of the extended amygdala that are dopamine D1 receptor rich, but have variable dopamine-like terminal input. In addition, we identified a complimentary distribution of the micro-opioid receptor 1, which also receives variable opioid peptide terminal input. We proposed a model in which the regions lacking direct terminal input maintain a tonic inhibition of amygdaloid fear outputs, whereas the regions receiving direct dopaminergic input disinhibit amygdaloid behavioural outputs, enhancing fear response. Following on from these brain circuitry studies we turned our attention to the critical developmental regulators of the monoamine fear circuitry. We first examined how a Parkinson's disease mutation in the transcription factor NURR1, might lead to impairment in dopamine development that may also affect fear circuitry. We also investigated, in vivo and in vitro, two transcriptional regulators that control development of the serotonin system (Pet-1 and Hes1) and how they impact serotonergic modulation of receptor expression. In vitro we showed Pet-1 and Hes1 directly enhance or repress, respectively, the expression of serotonin-1A receptors. Using mouse models lacking Pet-1, which specifically promotes serotonergic differentiation, we found unexpected compensatory alterations in the regulation of pre- and post-synaptic serotonin-1A receptors. In mice lacking Hes1, which restricts neuronal differentiation, we observed striking up-regulation receptor expression. Taken together, these studies provide (1) an anatomical template for understanding how emotionally relevant stimuli, including the subjective experience of stress, are processed by the extended amygdala, the core of the monoamine fear circuitry and (2) a molecular explanation for how this processing machinery may be predisposed to certain emotional or behavioural responses via early developmental regulatory events.
Keywords: Biology, Molecular.; Biology, Neuroscience.